Development and Life History of Sitophilus zeamais (Coleoptera: Curculionidae) on Cereal Crops - James Adebayo Ojo; Adebayo Amos Omoloye (Advances in Agriculture)
The maize weevil, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae), is one of the most destructive pests of stored cereals. Knowledge of the life history and biology is important to the development of an integrated pest management program. Investigation was carried out on developmental biology of S. zeamais on four main cereal crops, maize, rice, sorghum, and millet, under laboratory conditions. Egg incubation, oviposition periods, and larval instar development were not different significantly among the food hosts. Number of eggs laid varied significantly among the cereal grains; mean fecundity was highest on maize (67.2±3.16) and lowest on millet (53.8±0.17). Number of immature (larva and pupa) and adult stages varied significantly among the cereal grains. There exist four larval instars with a varied mean head capsule width, with a mean total instar larval developmental period of 23.1, 22.2, 22.2, and 21.6 d on maize, rice, sorghum, and millet, respectively. There was linear relationship and significant correlation between the stages of larval development and head capsule width. The mean developmental period from egg to adult varied, being highest on maize (34.7 d) and lowest on sorghum (33.5 d).